2011
DOI: 10.1007/s00406-011-0234-2
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes of fractional anisotropy in Alzheimer’s disease patients treated with galantamine: a 12-month randomized, placebo-controlled, double-blinded study

Abstract: Diffusion tensor imaging (DTI) demonstrates decline of fractional anisotropy (FA) as a marker of fiber tract integrity in Alzheimer's disease (AD). We aimed to assess the longitudinal course of white matter microstructural changes in AD and healthy elderly control (HC) subjects and to evaluate the effects of treatment with the cholinesterase inhibitor galantamine on white matter microstructure in AD patients. We enrolled 28 AD patients and 11 healthy elderly control subjects (HC). AD patients were randomly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 55 publications
1
15
1
Order By: Relevance
“…In addition, the effects of medication on WM structure changes were not investigated because all participants were drug-naive. In fact, a previous DTI study showed that FA decline was preserved in the posterior body of the corpus callosum in the AD group with galantamine treatment compared to the placebo group [36].…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the effects of medication on WM structure changes were not investigated because all participants were drug-naive. In fact, a previous DTI study showed that FA decline was preserved in the posterior body of the corpus callosum in the AD group with galantamine treatment compared to the placebo group [36].…”
Section: Discussionmentioning
confidence: 93%
“…Finally, if our interpretation of sprouting of collateral fibers is correct, this phenomenon is expected to reduce rather than increase the FA locally. This might have mitigated the expected effect of Galantamine (FA preservation) in the study conducted by Likitjaroen et al [Likitjaroen et al, ].…”
Section: Discussionmentioning
confidence: 96%
“…Negative findings were obtained in a DTI study in which 25 mild AD patients, 14 active and 11 with placebo, were treated with galantamine for 6 months with a further open-label extension of 6 months [61]. In this study, fractional anisotropy values were significantly maintained in the posterior part of the corpus callosum in the AD-treated subgroup at 6-months follow-up, but there was no difference between the treated and placebo groups at 12-months follow-up.…”
Section: Diffusion Tensor Imagingmentioning
confidence: 95%